Pengaruh Stres Dan Konflik Terhadap Kinerja Karyawan Dengan Semangat Kerja Sebagai Variabel Moderasi - Wawan Ariansya; Rahmat Laan; Burhanudin Gesi (Program Studi Manajemen - Fakultas Ekonomi - Universitas Muhammadiyah Kupang, 2019)
This study aims to determine the effect of stress and conflictpartially or simultaneously on the performance of employees of PTSimpatindo Multimedia Kupang with work spirit as a moderatingvariable. The number of samples are 104 employees. Data analysisuses multiple linear regression analysis. The results showed stressand conflict negatively affected the performance of employees ofPT Simpatindo Multimedia Kupang. Work spirit does not mediatethe effects of stress and conflict on employee performance.